Antioxidant activity and green synthesis of selenium nanoparticles using allium sativum extract - Jay Vyas; Shafkat Rana (International Journal of Phytomedicine, 2017)
The green synthesis of nanoparticles has provided cost effective, environment friendly procedure and raising safe strategies for synthesis of non-materials. In this study we investigated the clove of Allium sataivum, which is used for the synthesis of Selenium nanoparticles. The biosynthesized selenium nanoparticles were characterized by using UV-Visible (UV-VIS) spectrophotometer, Transmission electron microscopy (TEM), Fourier transform spectroscopy (FT-IR) and Energy dispersive X-Ray spectroscopy (EDAX). The selenium nanoparticles synthesized by garlic were observed as hollow and spherical particles in size ranging 7-45nm which is found more stable more than two months. The present study also reports the efficiency of ABTS, DPPH and FRAP assay to estimate the antioxidant potential of selenium nanoparticles which synthesized by garlic extract.